THE USE OF PROJECT-BASED LEARNING TO IMPROVE THE STUDENTS’ SPEAKING SKILL AT UNIVERSITAS ABULYATAMA - Cahyana, Putri; Dauyah, Ema; Meutia, Putri Dini; Susiani, Rini (Center for Research and Community Service (LPPM) University of Abulyatama, 2022)
Abstract: The objective of this study is to know the use of Project-Based Learning to improve the students’ speaking skill at the students of third semester of Abulyatama University. The study was quantitative approach which used pre-experimental research. This study only took eight students as sample of the research by using purposive sampling technique. The sample was divided into two groups, namely Group A and Group B. The instruments used in this study were pre-test and post-test. The result of the study showed that the use of Project-Based Learning can improve students’ speaking skill. It can be proven by the t-test result and the students’ scores on pre-test and post-test. It can be seen based on the mean in pre-test of the Group A was 62.5 and mean in post-test was 90. While the mean in pre-test of Group B was 50 and mean in post-test were 65. Based on the result of the computation of statistical hypothesis test, the students’ speaking score can be calculated by using t-test with significance α = 0.05. It indicated that the difference was significant because the t-test result was higher than the t-table (3.81 > 2.92). The students’ scores based on the Group A result was indeed better than their scores in Group B which indicates that the treatment contributes the students’ speaking skill as seen from the scores difference. In other words, it can be concluded that the Project-Based Learning was able to improve students’ speaking skill. The project provides opportunity to the students to become more creative and engaged in the interaction. The Project-Based Learning can be promoted by the teacher as a teaching method to English speaking skill.